DIKLAT PENGUATAN KEPALA SEKOLAH KECAMATAN TULANGBAWANG GUNA TERWUJUDNYA STUDENT WELLBEING - Irfan, Muhammad; Hadi, Samsul (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Diklat Penguatan Kepala Sekolah aims to improve the competence of school principals in accordance with their duties and functions, and encourage school principals to create independent schools to improve student learning outcomes which lead to the realization of student wellbeing. Diklat Penguatan Kepala Sekolah is held for 71 hours of lessons @ 45 minutes, online via the website: https://sim.tendik.kemdikbud.go.id/penguatanks. Prior to the implementation of the training, participants took the LMS introduction stage by the LMS admin for 6 jp. Training is held for 23 days. The service team consists of three people, namely 1 teacher, 1 LMS admin, and 1 LMS operator. Participants will get a Certificate of Completion of Education and Training (STTPP) with the results according to the predicate, if: (1) have completed the entire series of School Principal Strengthening Training activities, (2) meet at least 95% attendance, and (3) complete all assignments and bill. The implementation of the training to strengthen school principals in Tulang Bawang Regency, Tulang Bawang District was in accordance with the plan. Participants participated in the entire series of training activities enthusiastically and completed all given assignments properly and on time. After carrying out all stages of training to strengthen school principals, the results of the assessment were obtained. Based on the results of the assessment, it was found that all training participants passed and were entitled to a Certificate of Completion of Education and Training (STTPP). Abstrak. Diklat Penguatan Kepala Sekolah bertujuan untuk meningkatkan kompetensi kepala sekolah sesuai dengan tugas dan fungsinya, dan mendorong kepala sekolah untuk menciptakan sekolah merdeka demi tercapainya capaian belajar peserta didik yang bermuara pada terwujudnya students wellbeing. Diklat Penguatan Kepala Sekolah diselenggarakan selama 71 jam pelajaran @ 45 menit, secara daring melalui website: https://sim.tendik.kemdikbud.go.id/penguatanks. Sebelum pelaksanaan Diklat, peserta mengikuti tahap pengenalan LMS oleh admin LMS selama 6 jp. Diklat dilaksanakan selama 23 hari. Tim pengabdi terdiri dari tiga orang yaitu 1 pengajar, 1 admin LMS, dan 1 operator LMS. Peserta akan mendapatkan Surat Tanda Tamat Pendidikan dan Pelatihan (STTPP) dengan hasil capaian sesuai predikat, jika: (1) telah menyelesaikan seluruh rangkaian kegiatan Diklat Penguatan Kepala Sekolah, (2) memenuhi kehadiran minimal 95%, dan (3) menyelesaikan seluruh tugas dan tagihan. Pelaksanaan diklat penguatan kepala sekolah di Kabupaten Tulang Bawang, Kecamatan Tulang Bawang telah sesuai dengan rencana. Peserta mengikuti seluruh rangkaian kegiatan diklat dengan antusias dan menyelesaikan seluruh tugas-tugas yang diberikan secara baik dan tepat waktu. Setelah melaksanakan seluruh tahapan diklat penguatan kepala sekolah, diperoleh hasil penilaian. Berdasarkan hasil penilaian, diperoleh bahwa seluruh peserta diklat dinyatakan lulus dan berhak memperoleh Surat Tanda Tamat Pendidikan dan Pelatihan (STTPP).